A new species of Chiloschista (Orchidaceae, Aeridinae) from Myanmar - Wojtas, K. Philip; Bandara, Champika; Kumar, Pankaj (Phytotaxa, 2023)
A new species of Chiloschista is described and illustrated from Myanmar (Shan State) with colour plates, line drawing and photographs. The comparison and differentiation are made with Chiloschista rodriguezii, C. parishii and C. lunifera. Chiloschista shanica is most similar to C. rodriguezii from which it differs in having brownish streaks on green coloured peduncle and pedicel, densely placed flowers on the peduncle; sepals and petals comparatively shorter and wider, white coloured dotted with reddish-brown spots and being glabrous on the outer surface; labellum sac pointing forwards; side lobes of labellum acute with denticulate margin and arching above the column and denticulate upper margin of rostellum. From C. parishii and C. lunifera the new species differs in having a deeply saccate labellum with hairs on its front and back wall and sepals and petals almost glabrous on outer surface.